Public policies, sustainability, and smallholder producers' access to the market. The Productive Alliance Programme in Chile: A case study - Castillo, Mayarí; Pérez-Silva, Rodrigo; Chamorro, Catalina; Sepúlveda, Macarena (Frontiers in Sustainable Food Systems, 2022)
This study analyses the role of Chile's Productive Alliance Programme (PAP) in increasing welfare and improving access to the market for smallholder producers, by developing a sustainable agriculture in both social and environmental terms. This programme started in 2007 under the Ministry of Agriculture and now serves 3,600 smallholders in Chile. It seeks to create commercial partnerships between these smallholders and large companies, providing subsidies to establish conditions that allow the farmers to build new capabilities and skills. This case study used qualitative methodology and carried out 36 semi-structured interviews over July and August 2020. Interviewees included companies and smallholder producers within different productive chains, as well as public officials. The purpose of this analysis is to discuss the opportunities family farmers have to become a fundamental link in the supply chain of competitive companies at the national and international level. By providing targeted training on market requirements, agricultural management, risk management and sustainable use of resources, the programme enables smallholder producers to establish stable commercial alliances, improving their productive and management capacity. Although the programme's main outcome is not related to a significant increase in smallholders' income, participants perceive more stable earnings, reduced uncertainty, and improve their productive skills, mainly in terms of management and sustainable farming practices.